Optimizing Acid Mine Drainage Treatment Using Fly Ash and Bottom Ash - Oktaviansyah, Ikbal; Piestie Hawa (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2025)
Acid mine drainage (AMD), characterized by high acidity and elevated concentrations of heavy metals, poses a significant threat to aquatic ecosystems. This study aims (1) to analyze and optimize the effects of fly ash (FA) and bottom ash (BA) on the reduction of pH, Fe, Mn, and total suspended solids (TSS) through adsorption processes, and (2) to evaluate the impact of varying adsorbent mass ratios in determining optimal treatment efficiency. Adsorption experiments were conducted using 10, 20, and 30 g of FA, BA, and their combinations, with surface morphology characterized via scanning electron microscopy (SEM). The results demonstrated that 30 g of BA achieved the highest removal efficiency, increasing pH from 2.8 to 7.5, reducing Fe from 12.2 mg/L to 1.6 mg/L, Mn from 7.9 mg/L to 0.9 mg/L, and TSS from 40 mg/L to 5 mg/L. SEM analysis revealed that BA possesses a higher pore density and carbon content than FA, offering a greater number of active sites for adsorption. The t-test indicated that the individual and combined effects of FA (X1), BA (X2), and their mixture (X3) significantly influenced treatment performance. An adjusted R² value of 83.9% confirmed a strong correlation between adsorbent variables and improvements in AMD quality.